NUOVI DATI SUI GASTROTRICHI MARINI DELLA SICILIA - Todaro, Antonio (Biologia Marina Mediterranea, 2024)
So far, around 40 marine gastrotrichs species have been reported from Sicily. In September 2022, we performed new investigations, focusing on the coast of the Sicily Channel and the Gulf of Mondello. Ten locations were investigated, taking 1-2 liters of sediment from each. Taxonomic analysis was conducted on-site using Nomarski microscopy. Altogether, over 40 species were found, averaging 11 ± 6.8 species per location. The locality Le Solette (Menfi, Agrigento) was the richest, with 22 species, followed by Mondello (Palermo) with 19 species. Overall, the fauna documented in 2022 was made up mostly of species already known for Sicily, but there are also novelties, both at a regional level and in an absolute sense. Our results indicate that knowledge of the gastrotrich fauna of Sicily is incomplete and encourage us to continue research along other poorly investigated coastal stretches of the island.